Integrasi Pendidikan Islam dan Sains Perspiktif Amin Abdullah - Marjuki Duwila; Roisul Habib (STAI Attanwir Bojonegoro, 2021)
This article contains the concepts of integrating Islamic education and science in the world of education today in order to reduce a conflict between general science and religious knowledge in Indonesian education institutions. Currently the phenomenon of you being religious, many feel dissatisfied with the modern era that was happening so that there are still many religious people who openly reject modernity and miss the Islamic world that once triumphed in the past then applied in the current era with the aim of improving the problems that occur today. Besides that, there are also modernists who reject the existence of religion in the public sphere because religion has a dogmatic and closed mindset. Apart from that, Amin Abdullah was one of the figures who are trying to take a middle line to bring together scientists and clergy by using the idea of ​​integration-interconnection as foundation in carrying out reforms in the world of education